Physics identity of Asian identified US college students - Linda Zhang; Madison Swirtz; Kerstin Nordstrom (Physical Review Physics Education Research)
Asian(American) physics students lack ample representation in physics identity studies and in the broader science, technology, engineering, and mathematics (STEM) sociological literature. This may be due to their perceived overrepresentation, the “model minority” myth, or their treatment as monolithic. These misconceptions obscure the diversity among Asian(American) students. How do these students understand and form their physics identity? Through in-person interviews, we have gathered data on the experiences of self-identifying Asian or Asian American undergraduate physics majors. For our analysis, we draw from previous physics identity research and use the critical physics identity framework developed in recent studies on Black physicists’ identities. We present results from the ideational resource code and emergent codes generated from the data, such as Transnational Context and Asianization. Our findings suggest that some participants found other personal and social identities beyond their race or ethnicity to be salient to their physics identity and experience. Our results also indicate that the perceptions of Asian(Americans) as overrepresented in STEM may also serve to hide the less privileged identities that some of the participants hold and thereby the challenges that come with those less visible identities.